Does lipid peroxidation and oxidative DNA damage differ in cryopreserved semen samples from young, adult and aged Nellore bulls? - Trevizan, Juliane Teramachi [UNESP]; Carreira, Janaina Torres [UNESP]; Carvalho, Isadora Resende [UNESP]; Kipper, Bruna Helena [UNESP]; Nagata, Walter Bertequine [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Franco Oliveira, Maria Emilia [UNESP]; Pierucci, Julia Cestari [UNESP]; Koivisto, Marion Burkhardt de [UNESP] (Elsevier, 2018)
The aims of this study were to evaluate cryopreserved semen of Nellore bulls of different ages and verify whether sperm quality declines with advancing age and whether lipid peroxidation and DNA damage are involved in this process. For this purpose, 40 Nellore bulls were divided into three age groups: Young, aged 1.8–2 years (n = 9); Adult, aged 3.5–7.0 years (n = 19); and Seniors, aged 8.0–14.3 years (n = 12). Three ejaculates were collected from each bull, cryopreserved and evaluated for various parameters including membrane integrity, mitochondrial potential (FITC-PSA and JC1), lipid peroxidation (C-11BODIPY 581 / 591) and oxidative DNA damage (8OHdG) using flow cytometry. The thawed semen of senior bulls was characterized by a low percentage of motile sperm (33.7 ± 6.1%), higher damage to the plasma and acrosomal membrane (37.5 ± 9.8%), and low mitochondrial potential (29.1 ± 13.8%), as well as higher percentages of peroxidated cells (53.6 ± 12.2%) and DNA damage (44.1 ± 11.0%; P < 0.05). Lipid peroxidation was negatively correlated with motility (r = −0.35, P < 0.0002), average mitochondrial potential (r = −0.42; P < 0.0001) and showed a positive correlation with membrane injury and oxidative DNA damage (r = 039; P = 0.0003). Young bulls presented superior thawed sperm quality, possibly due to greater resistance to oxidative stress and, consequently, to cryopreservation. In conclusion, the sperm quality of bull semen declines with advancing age and is strongly associated with increased oxidative damage to both the plasma membrane and DNA.
Keywords: Aging; Cryopreservation; Reactive oxygen species (ROS); Sperm freezing